Feminist participatory methodologies in geography: creating spaces of inclusion - Caretta, Martina Angela; Riaño, Yvonne (My University, 2016)
This introduction prefaces a special issue on the topic of feminist participatory methodologies in geography. Drawing upon the experiences of the contributors in developing new tools and methods to facilitate interaction with participants and working with groups that tend to be forgotten, subordinated and/or alienated, we argue for the methodological significance of instating a feminist perspective to participatory research. Although much theoretical debate has taken place among feminist and post-colonial scholars on unequal research relationships between ‘researchers’ and ‘research subjects’, the literature on how to operationalize greater equality remains quite limited. We attempt to fill this research gap by bringing together scholars working in both the Northern and Southern hemispheres in order to illuminate the multifaceted ways in which these methods can be used not only to debunk hierarchical research relationships, but also to produce new scientific insights with greater validity.
Keywords: ethnography; feminist methodology; geography; participatory methods; spaces of inclusion